A Radiography of the Communication Industry in Costa Rica: A Radiography of the Communication Industry in Costa Rica - Carazo Barrantes, Carolina (2018)
This article presents a general analysis of the communication industry in Costa Rica and aims to be a way to approach a better understanding of the future of this area and the profession. The study, a survey of 100 companies in the sector, gives clues about how the communication industry is constituted in the country (sizes of companies, geographic scope, number and profile of collaborators, among others) and what its contributions to the national economy are (billing, out-sourcing and pro-bono work). As this is an exploratory study, it is expected that the findings will stimulate discussion in the industry and in the academic community and that this will result in the generation of future studies of greater depth.